Évaluation d’un atelier pour professionels d’aide désirant s’impliquer avec une structure d’entraide - Limoges, Jacques (Canadian Journal of Counselling and Psychotherapy, 2011)
Eighteen helping professionals, equivalent to 31% of a population, participated in a workshop follow-up concerning qualified mutual help. The study points out the main characteristics about some issues of the subjects, before, during, and after the workshop. Workshop strengths and weaknesses are raised and some improvements are indicated. As a by-product, it is a quick survey of some mutual help experiences in Québec.